2015
DOI: 10.1111/jora.12233
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Substance Use: Onset and Adverse Outcomes Among North American Indigenous Adolescents

Abstract: North American Indigenous communities experience disproportionately high rates substance use, abuse, and dependence and their accompanying consequences. This study uses group-based trajectory modeling of past-year substance use (alcohol, marijuana, and cigarettes) with a longitudinal sample of Indigenous adolescents from the northern Midwest and Canada (spanning ages 10 to 18 years). The early-onset trajectory (36.3%) had more adverse psychosocial difficulties at baseline than the mid-onset group (38.3%); both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…For example, in a study of First Nations youth living on-reserve in the United States, earlier age of first substance use predicted developmental course and increased risk of later psychological outcomes. 72 The potential synergistic or additive effects of having both parents who attended, and/or of having a grandparent who attended, were also not considered in the analyses. 8,20 Finally, research in animal and human studies demonstrating the moderating influence of the parental sex in determining the transmission of risks and protective factors to their sons and/or daughters raises the potential importance of considering parental gender in future analyses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of First Nations youth living on-reserve in the United States, earlier age of first substance use predicted developmental course and increased risk of later psychological outcomes. 72 The potential synergistic or additive effects of having both parents who attended, and/or of having a grandparent who attended, were also not considered in the analyses. 8,20 Finally, research in animal and human studies demonstrating the moderating influence of the parental sex in determining the transmission of risks and protective factors to their sons and/or daughters raises the potential importance of considering parental gender in future analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the first eight waves reveal that the children had low rates of SU and problem behaviors early in the study (around age 10 years), but also experienced high levels of early‐onset SU and mental health problems as they entered adolescence (Walls, Sittner Hartshorn, & Whitbeck, ). The study team identified several culturally relevant risk factors (e.g., historical trauma and losses, discrimination) and protective factors (e.g., enculturation; Walls, Whitbeck, & Armenta, ), along with within‐sample variability in SU trajectories over time (Sittner, ). After a lapse in funding spanning several years, annual interviews with the original adolescent participants (now in their mid‐20s) resumed in 2017, with plans for three total young adult assessments.…”
Section: Community Settingsmentioning
confidence: 99%
“…As such, we would also expect there to be a modest overlap in lifetime nicotine, alcohol, and marijuana use disorders across the course of adolescence. Among Indigenous youth, early onset substance users are more likely to proceed to multiple dependencies than are later onset substance users (Sittner, 2016). National data indicates that American Indian adults have among the highest rates of comorbid nicotine dependence and alcohol use disorders, and comorbid alcohol use disorder and other drug use disorders, particularly marijuana use disorder (Falk et al, 2006;Falk, Yi, & Hiller-Sturmhofel, 2008).…”
Section: Sud Comorbiditymentioning
confidence: 99%
“…High rates of lifetime SUD found among various Indigenous populations may be a function of early and cumulative abuse/dependence cases, rather than sustained risk across the life course (Copeland et al, 2017). Despite this, SUDs in adolescence likely disrupts key developmental processes (e.g., school, family relations) that may portend negative outcomes across the life course such as low educational attainment and criminal justice system involvement (Sittner, 2016).…”
Section: Timing and Probability Of Sud Onsetmentioning
confidence: 99%
See 1 more Smart Citation